Investigating solutions that improve Islanding resilience for the Snæfellsnes transmission system - Anton, Laurentiu Lucian, 1993- (2018)
Data used in this work is courtesy of Landsnet. The Icelandic transmission system is a network with a large central loop, numerous subnetworks, and radial lines connecting to smaller areas. Areas that are highly dependent on their radial transmission lines become particularly susceptible to radial disturbances. Further, islanding resilience of a radial area is defined by its response to failures on its radial line. The study of potential solutions for improving islanding resilience for radial areas is thus of great interest in Iceland. Due to it’s susceptibility to islanding under harsh weather conditions, Snæfellsnes was chosen as the case study for this research, which investigates potential infrastructure improvements that increase islanding resilience, along with their social, environmental and financial implications. This research begins by analysing the area, creating a power system model, validating said model and then analysing the model to set the stage for system modifications. The modification scenarios created were the addition of a 66-kV feed-in line, the use of Under-Frequency Load Shedding, the use of Islanding-Based Load Shedding, the addition of a quick-start back-up diesel generating station, and the addition of a battery storage facility. Of these, all solutions except the Under-Frequency Load-Shedding and the addition of a back-up generating station schemes eliminated islanding outages. The addition of the 66-kV feed-in line proved to be highly effective but required the largest investment. The most cost-effective solution was the Islanding-Based Load Shedding scheme, though this resulted in reduced load serviced. Lastly, the battery storage facility proved to be the best overall solution, which allowed for full service in the case of islanding, with minimal dynamic transients and similar costs to the back-up generating station. In addition, its minimal environmental impact, expected positive social response, and additional functionality make the battery storage facility the leading ...